Resistance and heteroresistance to colistin among multidrug-resistant and extensively drug-resistant Gram-negative organisms isolated from patients admitted to Zagazig University Hospitals - Ali, Salah Al-Sayed Ibrahim; Ghamry, Aya Ahmed; Khirala, Seham K; El-Nasser, Asmaa M; Al-Sayed, Fatma M Attia; Ibrahim, Fatma Atef (The Journal of Infection in Developing Countries, 2025)
Introduction: Nowadays, treating serious infections caused by multi-drug resistant Gram-negative bacteria is best left to the antiquated medication "colistin.". There have been reports of colistin-resistant (Col-R) and heteroresistant (hR) MDR and XDR-GNB strains worldwide. Therefore, we aimed to ascertain the rate of colistin resistance, certain potential resistance mechanisms, and heteroresistance in colistin-susceptible (Col-S) clinical isolates. Methodology: Identification and Antibiotic susceptibility test (AST) for all isolates were determined by Vitek-2 automated system. The Col-S strains were evaluated for heteroresistance using the population analysis profiling (PAP) method, while the Col-R strains were tested for mcr-1 gene activity by combined disk test (CDT) and colistin minimum inhibitory concentration reduction (CMR) test. The efflux pump mechanism was identified using cyanide 3-chlorophenylhydrazone (CCCP). Results: Out of 60 isolates enrolled in the study, AST revealed that 60% were MDR-GNB and 40% were XDR-GNB. Ten isolates were colistin resistant (16.6%). The mcr-1 gene was detected in five (5/10) Col-R isolates by PCR. CDT test detected mcr-1 gene activity in four (4/5) of mcr-1 gene positive isolates, while CMR test detected all. Efflux pump inhibition by CCCP showed a reduction of MICs by ≥ 8-folds in four Coli-R isolates. The frequency of carbapenem resistance (CR) within Col-hR strains was 75%, while ESBL was 25%. Conclusions: The alarmingly high occurrence of colistin resistance and heteroresistance in hospital care settings is of major concern and necessitates a reassessment of recommended AST methods since it can result in colistin therapy failure.